Unchanging witness : the consistent Christian teaching on homosexuality in scripture and tradition - Fortson, S. Donald (Samuel Donald), 1956-; Grams, Rollin Gene, 1958- (Nashville, B&H Academic, 2016)
"The church is going through a time of severe fracture over the issue of homosexuality. This book addresses the arguments from the gay Christian movement and revisionist theologians and exegetes on a single point: Can they withstand the evidence of the primary sources? In Unchanging Witness, Donald Fortson and Rollin Grams articulate the consistent orthodox view on homosexuality by presenting primary sources throughout Christian history and by interpreting the biblical texts in their cultural contexts. The first part of the book examines church history from the patristic period to the present day, and the second part engages biblical texts in light of ancient Near Eastern, Jewish, Greek, and Roman primary sources"--Back cover.
The Gay Christian Movement -- Church Fathers and a Distinct Christian Life -- The Middle Ages and Confessing Sin -- Renaissance and Reformation Confront Immortality -- Roman Catholics and the Orthodox on Historic Faith -- Evangelicals on Scripture and Conversion -- Mainline Denominations and Revisionist Christianity -- Sexual Ethics in Scripture and the Early Church -- The Old Testament Texts Addressing Homosexuality -- Sodom's Sins -- Homosexuality in the Ancient Near East -- Jewish Views on Homosexuality after Old Testament Times -- The New Testament Texts Addressing Homosexuality -- Law, Holiness, and Purity for God's People: 1 Corinthians 5-7 -- "Soft Men" and "Homosexuals" in 1 Corinthians 6:9 -- Homosexual Orientation in Antiquity and in Paul's Writings -- Paul's Nature/Creation and Nurture/Law Argument in Romans -- Revisionist Readings on Romans 1:24-28.
Includes bibliographical references and indexes.
Keywords: Homosexuality -- Religious aspects -- Christianity; Homosexuality -- History of doctrines; Homosexuality -- Biblical teaching